Surface detail - Banks, Iain, 1954- (London : Orbit, 2010)
When sex slave Lededje Y'breq is murdered by a politician on the planet Sichult, the artificial intelligence running one of the Culture's immense starships resurrects her so she can seek revenge. Meanwhile, the Culture is uneasily watching the conflict over whether to preserve virtual Hells for the souls of "sinners" or give them the release of death.
"A Culture novel"--Jacket.
Keywords: Artificial intelligence -- Fiction; Life on other planets -- Fiction; Revenge -- Fiction; Science fiction